Hemodynamics during Rotary Blood Pump support with speed synchronization in heart failure condition: A modelling study - Zwe Lin Htet (2018)
© 2015 IEEE. The aim of this work is to study the hemodynamic changes in the cardiovascular system under different modes of Rotary Blood Pump (RBP) support. Continuous mode (constant pump speed) and co-pulse mode (increased pump speed in systole) are studied. Computer simulation studies have been conducted to evaluate the performances of these two modes under normal and pathological conditions. The pathological heart condition is simulated by reducing the maximum systolic elestance (Emax) in the cardiovascular system model. The model is implemented by using MATLAB Simulink. The pressure-volume loop of different heart conditions (normal heart: 100% of normal contractility, pathological heart: 30% of normal contractility) and the different modes of RBP support (8krpm and 11krpm in continuous mode, between 8krpm and 11krpm in co-pulse mode) are simulated. The results of this study show the slope of end systolic pressure volume relationship (ESPVR) changes in pathological condition. The reduction of area inside pressure volume loops depend on the increasing level of pump speed. The results indicated systolic aortic pressures in co-pulse mode are higher than in the continuous mode. In normal condition, the value of systolic aortic pressure in co-pulse mode is 113 mmHg and the values of systolic aortic pressures in continuous modes are 109 mmHg (8k) and 95 mmHg (11k). In pathological condition, the value of systolic aortic pressure in co pulse mode is 100 mmHg and the values of systolic aortic pressures in continuous modes are 90 mmHg (8k) and 95 mmHg (11k). The hemodynamics results of this study are comparable in vivo data, clinical data and other simulation studies. Therefore, this simulation enables hemodynamic studies in patients with end-stage heart failure, and patients under different modes of rotary blood pump support